Theoretical investigation of plasmonic-dielectric mode coupling in multi-core photonic crystal fibers - Ma, Ming (2015)
With the rapid progress of research into surface plasmon polaritons based nanophotonics, investigations of plasmonic waveguides are currently being carried out. There are many potential applications in this area, and a good example would be photonic integrated circuits. However, due to the absorption present in metals, plasmonic nanostructures usually have high losses. As a result, transferring signals only by plasmonic waveguides is impractical. Therefore, it is increasingly important to implement seamless combination between plasmonic waveguides and low-loss, dielectric waveguides. In this project, this goal is achieved through investigation of asymmetric directional coupling between a hybrid plasmonic waveguide and another dielectric waveguide. And such a plasmonic-dielectric waveguide structure has properties of low loss and short coupling length.